2020
DOI: 10.13106/jafeb.2020.vol7.no6.297
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Managerial Efficiency of Insurance Companies in Saudi Arabia: A Data Envelopment Analysis Approach

Abstract: This paper applies the Data Envelopment Analysis (DEA) to compute the managerial efficiency of 30 insurance companies listed on the Saudi stock exchange for the duration of four years from 2015 to 2018. The companies taken as a sample of study included both conventional and Takaful insurance companies. The insurance sector of KSA is one of the largest sectors in the country, contributing a substantial percentage in the non-oil economy. Efficiency measurement and evaluation will provide a venue to introspect an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 36 publications
1
21
0
Order By: Relevance
“…The efficiency measurement of any production function of business is highly, significant for decision-making, further improvement and survival as a whole. As discussed in the literature review, the highly-recommended tool for efficiency studies is the DEA (Naushad et al 2020). Specifically, this study adopts DEA, which is a non-statistic model using liner programming.…”
Section: Data Envelopment Analysismentioning
confidence: 99%
“…The efficiency measurement of any production function of business is highly, significant for decision-making, further improvement and survival as a whole. As discussed in the literature review, the highly-recommended tool for efficiency studies is the DEA (Naushad et al 2020). Specifically, this study adopts DEA, which is a non-statistic model using liner programming.…”
Section: Data Envelopment Analysismentioning
confidence: 99%
“…Several authors like ; Ariff and Can (2008); Cummins & Xie (2008); and Lai et al (2011) applied two stages to estimate relative efficiency scores, used DEA or SFA in the first stage to determine the comparable efficiency scores followed by multivariate analysis as the second stage with a set of contextual internal (company-specific) and external variables related to environment and economy. There are very few studies based on GCC insurers in the existing literature, like (Almulhim & McMillan, 2019;Benyoussef et al, 2019;Naushad et al, 2020) based on Saudi Arabian takaful insurers. Rao et al (2010) measured the managerial efficiency of insurers in the UAE.…”
Section: Rationale Of the Studymentioning
confidence: 99%
“…The upcoming section discusses the hypothesized effect of firm-specific variables and external environmental variables on the insurers' technical efficiency scores. Naushad et al (2020) computed the managerial efficiency of 30 insurance companies listed on the Saudi stock exchange from 2015 to 2018. They have applied BCC and CCR models of DEA and revealed that a good number of insurance companies operating in KSA were found to be efficient on managerial efficiency scale.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Many countries where financial management is administered by Islamic Shariah are getting success by utilizing skilled personnel. The leading insurance companies in KSA emerged as the leader of the market in terms of managerial efficiency, and could be benchmarked by other companies operated in the market (Naushad, Faridi, & Faisal, 2020). One of the major challenges faced by the Islamic insurance companies in Bangladesh and many other countries is the lack of knowledgeable and qualified personnel.…”
Section: Shortage Of Skilled Personnelmentioning
confidence: 99%